Introduction: Sudbury's Crisis of Development and Democracy - Leadbeater, David (Mining Town Crisis: Globalization, Labour, and Resistance in Sudbury, 2008)
Analyzes Sudbury as a hinterland of resource extraction, including the response of unions. Provides new policy strategies for labour and an assessment of the community's future prospects.
https://fernwoodpublishing.ca/book/mining-town-crisis